Negative self-synchronization will i change to be like you when it is bad for me?. [article]. - Gabriel, Shira
The current research examined whether people will attempt to modify internal aspects to make them congruent with others, even when those modifications have negative implications for the self, a phenomenon we refer as negative self-synchronization. We propose that negative self-synchronization will occur only for individuals who are surely attached. Across 4 experiments, participants who were high in secure attachment were more likely that those low in attachment security to engage in negative self-synchronization (Experiment 1-4). Attachment style did not moderate positive synchronization (Experiment 1 and 2). In addition, priming secure attachment increased negative self-synchronization among insecure participants (Experiment 2 and 3). Conversely, priming insecure attachment decreased negative self-synchronization among secure participants (Experiment 4). Implications of these findings for social synchronization processes, the need to belong, and attachment security are discussed.
Keywords: Self-other overlap; Risk regulation; Automatic social behavior; Need to belong; Attachment